Committed anchor investment and IPO Survival – the roles of cornerstone and strategic investors - Espenlaub, Susanne; Khurshed, Arif; Mohamed, Abdulkadir; Saadouni, Brahim (Elsevier, 2016)
Recent U.S. policy encourages anchor investments to facilitate initial public offerings (IPOs) and increase companies' access to external finance. As access to external funds relies on stocks remaining listed, we study anchor investors' impact on how long IPOs stay listed. We examine two types of anchor investors in Hong Kong: strategic and cornerstone investors, that are similar to U.S. anchor investors, but show varying levels of commitment to the IPO. We find that IPOs backed by more committed investors, with longer post-IPO commitments (lockups), stay listed longer. This suggests that the success of U.S. policies may require investors' commitment.
Keywords: Anchor investment; IPO; Survival; Share allocation; Cornerstone investor; Strategic investor